2000
DOI: 10.1200/jco.2000.18.12.2385
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Comparative Study of Vinorelbine Combined With Doxorubicin Versus Doxorubicin Alone in Disseminated Metastatic/Recurrent Breast Cancer: National Cancer Institute of Canada Clinical Trials Group Study MA8

Abstract: The survival with DOX and VNB is not superior to DOX alone in MBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 25 publications
4
58
0
5
Order By: Relevance
“…The median duration of survival in the current study (21 months) was consistent with that in two of the previous studies (18 and 23 months) [18,19] and lower than that in the other two studies (27.5 and 31 months) [14,20]. The response rate (38%) and median survival (13.8 months) were lower when doxorubicin and vinorelbine were evaluated as first-or second-line therapy in a recent Canadian study [21]; outcomes were not specified for first-versus second-line therapy in that study. It is not surprising that fluorouracil and vinorelbine appeared to be associated with a shorter duration of survival (12 versus 21 months) than was doxorubicin and vinorelbine in the current study, given the fact that there were two distinct patient populations treated in this trial.…”
Section: Discussionsupporting
confidence: 79%
“…The median duration of survival in the current study (21 months) was consistent with that in two of the previous studies (18 and 23 months) [18,19] and lower than that in the other two studies (27.5 and 31 months) [14,20]. The response rate (38%) and median survival (13.8 months) were lower when doxorubicin and vinorelbine were evaluated as first-or second-line therapy in a recent Canadian study [21]; outcomes were not specified for first-versus second-line therapy in that study. It is not surprising that fluorouracil and vinorelbine appeared to be associated with a shorter duration of survival (12 versus 21 months) than was doxorubicin and vinorelbine in the current study, given the fact that there were two distinct patient populations treated in this trial.…”
Section: Discussionsupporting
confidence: 79%
“…Although survival is not a major end point for evaluation of efficacy in phase II trials, the median overall survival of 25 months in this study was favourably within the range of other previously reported major protocols of anthracycline-based regimens (Ross et al, 1985;Clavel and Catimel, 1993;Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), taxane-based regimens (Jassem et al, 2001;Biganzoli et al, 2002;Sledge et al, 2003), and vinorelbinebased regimens (Dieras et al, 1996a;Nole et al, 1997;Norris et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…Combining the results of this study with the two published reports DaunoXome has shown objective responses in eight out of 35 (23%) evaluable patients (Anonymous, 1996;Darskaia et al, 1999). The response rate for this relatively non-toxic anthracycline based therapy must be taken in context with those reported for single-agent doxorubicin which vary from 30 -34% in recent randomised phase III studies (Henderson et al, 1989;Sledge et al, 1997;Chan et al, 1999;Norris et al, 2000). The overall time to tumour progression of 5 months (8.5 months in those patients treated at 120 and 150 mg m 2 ) and median survival of 13.75 months are in keeping with the results reported for large randomised studies of doxorubicin when used alone or as part of a combination regimen in the treatment of symptomatic relapsed breast cancer (Norris et al, 2000).…”
Section: Discussionmentioning
confidence: 99%